Studying the Reversibility of Multielectron Charge Transfer in Fe(VI) Cathodes Utilizing X‑ray Absorption Spectroscopy - Farmand, Maryam; Licht, Stuart; Ramaker, David (Journal of physical chemistry. C, 2013)
The superiron salts BaFeO4 and K2FeO4 when utilized as battery cathodes both undergo a three electron charge transfer; however, they exhibit significantly different physical and electrochemical properties. K2FeO4 exhibits higher solid-state stability and higher intrinsic 3e– capacity (406 mAh/g) than BaFeO4 (313 mAh/g); however, the rate of cathodic charge transfer is considerably higher for BaFeO4. To understand these differences, primary coin cells of alkaline batteries containing either μm-BaFeO4, μm-K2FeO4, or nm-K2FeO4 (nm = nanometer, or μm = micrometer size particles) were constructed and discharged to various depths under a constant load. Discharged cathode composite were studied by ex-situ X-ray absorption measurements. The oxidation state of discharge product of the Fe local symmetry was followed by the magnitude of K-edge and pre-edge Fe 1s to 3d peak. To track structural changes, the extended X-ray absorption fine structure (EXAFS) χ functions of the partially discharged cathodes were subject to linear combination fitting. The expanded BaFeO4 lattice, or the much larger surface-electrolyte interface in the nm-K2FeO4 materials, significantly increased their capacities compared to μm-K2FeO4. In the case of nm-K2FeO4, electron density is more distributed by water intercalation about the Fe hydrous environment, which relieves the “stress” of full Fe6+ to Fe3+ reduction. The stronger Ba–FeO4 anion–cation interaction and increased lattice size apparently slows the rate of lattice rearrangement into the discharge product.